The Hybrid Model of Long Term Care to People in Dependency Situation in Spain: a Decade of Legislative Changes and Budget Adjustments - Martínez López, José Ángel (Revista del CLAD Reforma y Democracia, 2017)
Promotion of Personal Autonomy and Care for People in Dependency Situation Act 39/2006, is one of the most significant advances in social policy in the Welfare State in recent decades in Spain. This legal standard, in line with all European countries in our environment, seeks to respond mainly to the new demands for long-term care as a result of the increase in life expectancy in the population. One of the most novel aspects incorporated by act is the subjective right of citizenship to receive care. In this way, the role of the State in social protection is reinforced within a family model where families, especially women, have traditionally acted as care providers. Ten years after the adoption of the act, it is relevant in the analysis of the policies and public administration, to know the model of social protection of dependency that is being implemented nowadays. For that, we first approach aging of the population in advanced societies. Secondly, the most relevant theoretical contributions in relation to the configuration of the act and its overlap with social welfare regime in Spain. Then, the most important normative changes in the system of attention to dependency from the beginning of its application to the present time. Fourth, it is carry out an analysis of secondary data on act management. Finally, it is exposed what are the characteristics that identify the model of social protection of dependency in Spain.